Improving Student Understanding of Academic Assessment Vocabulary Words Using Visual Cues: A Collaborative Effort - Kim Soper; Jenenne A. Geske; Liliana Bronner; Maurice Godfrey (Journal of Community Engagement and Scholarship, 2022)
Many students have difficulty understanding terms from the academic register such as “analyze,” “discuss,” and “compare.” This issue may be exacerbated for some Native American students, especially those who live on reservations with limited exposure to mainstream cultures. In this community-based participatory research project, academic investigators partnered with educators and community members from Native communities in Nebraska and South Dakota to expand students’ academic vocabulary and improve student achievement. Together, we formed a team in which community members collaborated with academic investigators to develop word-wall cards incorporating dual-coding theory—that is, combining visual and verbal cues—to help students understand academic vocabulary words. Paivio’s dual-coding theory postulates that verbal and visual information are encoded in separate but interconnected pathways and that concepts encoded via both pathways are more easily remembered. Accordingly, presenting information using multiple mediums, such as graphs, photographs, or demonstrations, may enhance learning. These cards were shared with community educators who used them in their classrooms. We present evidence that incorporating these multimodal tools into classrooms may improve students’ understanding of academic vocabulary. Through this partnership, educators in Native American communities were able to represent their lived experiences. Teachers and administrators in Native American and non-Native classrooms could easily partner with other experts to incorporate similar innovations in their own schools and classrooms.